2013
DOI: 10.1080/09585192.2012.694110
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of pay settlements: the influence of the national context

Abstract: This article studies the influence of national context and collective bargaining on the factors taken into account when adjusting wages. Using data from Spanish and British manufacturing establishments, we examine the relative importance of the cost of living, the ability to recruit or retain employees, the financial performance of the organisation and the industrial relations climate on wage adjustments of manual workers at the establishment level. Our findings show that there are significant differences on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In what follows, this perspective on strike behaviour will be outlined. National contexts for – in particular – public sector strikes vary substantially (Bayo-Moriones et al, 2013), but the considerations presented here may nevertheless be of general interest.…”
Section: Public Sector Wage Relativities Coordination Problems and Smentioning
confidence: 99%
“…In what follows, this perspective on strike behaviour will be outlined. National contexts for – in particular – public sector strikes vary substantially (Bayo-Moriones et al, 2013), but the considerations presented here may nevertheless be of general interest.…”
Section: Public Sector Wage Relativities Coordination Problems and Smentioning
confidence: 99%
“…A wage is not solely determined by labor market forces as predicted by the model, but also by negotiations between employees and employers, as well as by political decisions. Raurich et al (2009) provided evidence on the factors influencing wage setting in the Spanish private sector, including variables such as employment level, real gross domestic product and average productivity as potential determinants of the minimum wage, while Bayo-Moriones et al (2013), claimed that there are two factors that drastically affect the level of the minimum wage: the per capita income per employee and the level of the average wage. Brutel (2019) found that the minimum wage in Germany has increased hours wages significantly while the effect on monthly salaries has been less substantial.…”
Section: Introductionmentioning
confidence: 99%